Semiconductor nanowire arrays for optical sensing: a numerical insight on the impact of array periodicity and density. (25th May 2021) - Zagaglia, Luca; Demontis, Valeria; Rossella, Francesco; Floris, Francesco
Abstract: Recent advances in the nanofabrication and modeling of metasurfaces have shown the potential of these systems in providing unprecedented control over light–matter interactions at the nanoscale, enabling immediate and tangible improvement of features and specifications of photonic devices that are becoming always more crucial in enhancing everyday life quality. In this work, we theoretically demonstrate that metasurfaces made of periodic and non-periodic deterministic assemblies of vertically aligned semiconductor nanowires can be engineered to display a tailored effective optical response and provide a suitable route to realize advanced systems with controlled photonic properties particularly interesting for sensing applications. The metasurfaces investigated in this paper correspond to nanowire arrays that can be experimentally realized exploiting nanolithography and bottom-up nanowire growth methods: the combination of these techniques allow to finely control the position and the physical properties of each individual nanowire in complex arrays. By resorting to numerical simulations, we address the near- and far-field behavior of a nanowire ensemble and we show that the controlled design and arrangement of the nanowires on the substrate may introduce unprecedented oscillations of light reflectance, yielding a metasurface which displays an electromagnetic behavior with great potential for sensing. Finite-difference time-domain numerical simulations are carried out to tailor the nanostructure parameters and systematically engineer the optical response in the VIS-NIR spectral range. By exploiting our computational-methods we set-up a complete procedure to design and test metasurfaces able to behave as functional sensors. These results are especially encouraging in the perspective of developing arrays of epitaxially grown semiconductor nanowires, where the suggested design can be easily implemented during the nanostructure growth, opening the way to fully engineered nanowire-based optical metamaterials.